MATEMATIKA DAN PEPUTIQ CINA SEBAGAI ADAT PERNIKAHAN SUKU MANDAR - eka purnamayanti (MEGA: Jurnal Pendidikan Matematika, 2024)
Culture can determine how students view things, including understanding mathematical material. Therefore, there is a need for a learning approach that is able to connect mathematics with culture, called Ethnomathematics. The concept of ethnomathematics makes a major contribution to improving mathematics learning. Ethnomathematics objects are cultural objects that contain mathematical concepts in a particular society, one of which is Peputiq China. One of the mathematical concepts contained in Peputiq Cina is the concept of geometry. This research aims to determine the various geometric concepts found in Chinese Peputiq. The method in this research uses qualitative research with an ethnographic research design. The data sources in this research use data from observation, documentation and interviews. This research aims to identify and describe the mathematical objects contained in the Chinese peputiq as one of the Mandar tribe's wedding customs. This exploratory research using an ethnographic approach is to explore the concept of geometric shapes in the creation of the Chinese peputiq frame. Through exploration, documentation, observation and interviews, geometric shapes can be found, both flat shapes and spatial shapes, including squares, rectangles, triangles, while geometric shapes include upright prisms and blocks.